2018
DOI: 10.1172/jci97611
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-mesenchymal transition leads to NK cell–mediated metastasis-specific immunosurveillance in lung cancer

Abstract: .(S4945; Sigma-Aldrich) with subsequent anti-rabbit-Alexa Fluor 488 (R37116) secondary antibody.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 57 publications
4
91
0
Order By: Relevance
“…Interestingly, a recent study indicates that after an epithelial-mesenchymal transition, tumor cells are particularly sensitive to NK cell killing, again suggesting that tumor cells are not equal in term of immunosurveillance (17). Based on our results, we propose that these cancer cell subsets with mesenchymal features, located at the periphery of tumor islets are more prone to stimulate CAR T cells through the expression of one or several proteins that remain to be identified…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, a recent study indicates that after an epithelial-mesenchymal transition, tumor cells are particularly sensitive to NK cell killing, again suggesting that tumor cells are not equal in term of immunosurveillance (17). Based on our results, we propose that these cancer cell subsets with mesenchymal features, located at the periphery of tumor islets are more prone to stimulate CAR T cells through the expression of one or several proteins that remain to be identified…”
Section: Discussionsupporting
confidence: 64%
“…Thus, for example, EMT has been shown to induce an immunosuppressive microenvironment in hepatocellular carcinoma (40), or to reduce the ability of breast cancer cells to form immunologic synapses with cytotoxic T lymphocytes (34). On the other hand, it has also been reported that EMT induction could promote NKG2D-L upregulation on colorectal cells and on immortalized keratinocytes, or induce increased NK cell-mediated metastasis-specific immunosurveillance in lung cancer (41,42). Nevertheless, besides HLA-I molecules, no major NK-receptor ligands were significantly modified by EMT in our experiments on melanoma cells ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Huergo-Zapico et al recently showed that NK-cells could mediate EMT programs in melanoma cells, simultaneously potentiating the immune resistance capacity of the latter. On the contrary, data from at least two studies using various model systems have raised the possibility that EMT induction could increase cancer cell susceptibility to NK cells through up-regulation of NKG2D ligands or cell adhesion molecule 1 (CADM1) [ 59 , 60 ]. This further highlights the contextual nature of the events.…”
Section: Impact Of Plasticity and Heterogeneity On Tumor Immune Esmentioning
confidence: 99%